(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the issues of translation from French into Uzbek, with an emphasis on linguistic and cultural features. The authors analyzed the key theoretical aspects of this topic and presented the results of the study. The analysis showed that French speech is saturated with politeness formulas, which gives it a certain tone. It was found that in business discourse, vocabulary with a broad meaning is often used, requiring special attention of the translator to select adequate and understandable equivalents. It also emphasizes the existence of three types of equivalence in translation: formal (similar linguistic means are used), semantic (meaning is conveyed using other means) and situational (different linguistic means describe the same situation).